STEM to STEM: Integrating Applied Mathematics with Visual Arts to Enhance Creative Thingking in Higher Education - Prabowo, Yani; Rozhana , Kardina Metha; Wicaksono, Antonius Alam; Sugiharto, Firsta Bagus; Maharjan, Kailie (Journal of Social Science Utilizing Technology, 2024)
Background. The integration of Science, Technology, Engineering, and Mathematics (STEM) with the Arts, forming STEAM, has gained attention as an approach to enhance creative thinking and interdisciplinary learning in higher education. While STEM disciplines emphasize analytical and problem-solving skills, the inclusion of visual arts fosters innovation and creativity, preparing students for complex, real-world challenges. Purpose. This study explores the integration of applied mathematics with visual arts as a STEAM approach to enhance creative thinking in higher education. Method. The research adopts a mixed-method design, combining quantitative and qualitative methods to assess the impact of a STEAM-based curriculum. A quasi-experimental study was conducted with 120 undergraduate students divided into experimental and control groups. The experimental group engaged in interdisciplinary projects combining mathematical modeling with artistic design, while the control group followed a traditional STEM curriculum. Creativity was measured using the Torrance Tests of Creative Thinking (TTCT) and student reflections. Results. The findings reveal that the experimental group demonstrated a 40% improvement in creative thinking scores compared to the control group. Qualitative data indicated that students in the experimental group exhibited greater engagement, motivation, and ability to connect abstract mathematical concepts with practical, creative applications. Challenges included time management and adapting to interdisciplinary methodologies. Conclusion. The study concludes that integrating applied mathematics with visual arts in a STEAM-based curriculum significantly enhances creative thinking. This approach fosters interdisciplinary collaboration, innovation, and engagement among students. Future research should explore its scalability across diverse educational settings and disciplines.